KREDIBILITAS INFLUENCER DALAM MEMPENGARUHI MINAT BELI KONSUMEN PRODUK SKINCARE MS GLOW DI KABUPATEN SUMBAWA - Ismawati, I; Safira, Manar Nabila (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to determine the credibility of influencers in influencing consumer purchasing interest in MS Glow skincare products in Sumbawa District. The type of this study was associative study which aims to examine the effect of influencer credibility (X) on consumer purchasing interest in MS Glow skincare products in Sumbawa District (Y). The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 50 consumers of MS Glow skincare products in Sumbawa District. Determination of respondents in this study used a non-probability sampling technique with the accidental sampling method. The data used in this study was processed using the SPSS application to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and coefficient of determination testing (R2). The results of this study indicate that influencer credibility had a positive and significant effect on consumer purchasing interest in MS Glow skincare products in Sumbawa District. The ability of the influencer credibility variable to effect on consumer purchasing interest in MS Glow skincare products in Sumbawa District was 63.5%, while the remaining of 36.5% was effected by other factors not examined in this study, such as price, location, product quality and service quality.